2015
DOI: 10.1007/s11250-015-0830-7
|View full text |Cite
|
Sign up to set email alerts
|

Liquid residue of cassava as a replacement for corn in the diets of sheep

Abstract: The effect of the replacement of corn with the liquid residue of cassava was evaluated at levels of 0, 25, 50, 75, and 100% in the diets of sheep on the intake and nutrient digestibility, weight gain, and carcass characteristics. Forty non-castrated crossbred Santa Ines sheep at 4 months of age and an initial body weight of 19.5 ± 2.5 kg were slaughtered after 90 days at the feedlot. A quadratic effect was found for intake of dry matter (DM), organic matter (OM), non-fiber carbohydrates (NFC), and digestible O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…These results evidenced the influence of energy intake on tissue deposition in sheep, with consequent gains in carcasses [ 13 , 14 ]. The maximum values for HCW and CCW found in this study (18.70 and 18.11 kg, respectively) meet the minimum values for carcass characterization with good quality, with HCWs equal to or greater than those obtained in studies using conventional diets with corn, soybean, and Tifton grass hay in their composition [ 15 , 16 ].…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…These results evidenced the influence of energy intake on tissue deposition in sheep, with consequent gains in carcasses [ 13 , 14 ]. The maximum values for HCW and CCW found in this study (18.70 and 18.11 kg, respectively) meet the minimum values for carcass characterization with good quality, with HCWs equal to or greater than those obtained in studies using conventional diets with corn, soybean, and Tifton grass hay in their composition [ 15 , 16 ].…”
Section: Resultssupporting
confidence: 61%
“…The 44% replacement showed much higher results than in other studies. Studies by [ 15 ] and [ 16 ] with Santa Inês animals fed conventional feeds composed of Tifton grass hay, corn, and soybean and using the same roughage:concentrate ratio [ 15 ] showed a SBW of 30.7 kg, HCW of 13.2 kg, and CCW of 12.7 kg. For SBW, HCW, and CCW, [ 16 ] found 34.7, 15.9, and 15.3 kg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…One study showed that diets with 15% cassava bagasse will make milk production increase 13.2% and its operational cost decrease 42.8%, compared to controls [6]. Using cassava residue (less than 20%) to replace maize in the dietary of Hu lambs could linearly improve its growth performance along with antioxygenic property and liver function were also affected [7]. One study indicated that using diet with 32% of cassava residue to feed lactating dairy cows at early lactation, their milk production reduced but the constituents of milk was not affected.…”
Section: Introductionmentioning
confidence: 99%
“…Every year, more than one million tons of wet-cassava residues are produced in Guangxi province, China, and they are utilized as animal feed (Dos Santos Filho et al 2015), substrate media for bacteria (Li et al 2012), and agricultural fertilizers (Duarte et al 2013). Therefore, the finding of more valuable uses for cassava residues is an important issue.…”
Section: Introductionmentioning
confidence: 99%